1983
DOI: 10.1029/jb088is02p0a731
|View full text |Cite
|
Sign up to set email alerts
|

Fluid inclusions in stony meteorites

Abstract: We describe fluid inclusions in five stony meteorites: diogenite ALHA 77256 and chondrites Bjurbole (H4), Faith (H5), Holbrook (L4), and Juin (H5). This brings to seven the number of stony meteorites in which fluid inclusions have been confirmed. The fluid inclusions in diogenite ALHA 77256 display a vapor bubble that decreases in volume from −180°C, the lowest temperature attainable in our microthermometric runs, to homogenization of liquid plus vapor to liquid. Homogenization temperatures are reproducible in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…The distribution and physical properties of these new fluid inclusions indicate they may be artifacts of thin section preparation; we suggest that saw coolant was sucked into vacuum vesicles in glasses and minerals through submicroscopic fractures produced during sawing. The similarities between these fluid inclusions and fluid inclusions previously described by Warner et al (1983) lead us to conclude that many of the fluid inclusions reported earlier may be artifacts. Consequently, the origin of any fluid inclusions observed in thin sections of extraterrestrial materials must be interpreted with caution.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…The distribution and physical properties of these new fluid inclusions indicate they may be artifacts of thin section preparation; we suggest that saw coolant was sucked into vacuum vesicles in glasses and minerals through submicroscopic fractures produced during sawing. The similarities between these fluid inclusions and fluid inclusions previously described by Warner et al (1983) lead us to conclude that many of the fluid inclusions reported earlier may be artifacts. Consequently, the origin of any fluid inclusions observed in thin sections of extraterrestrial materials must be interpreted with caution.…”
supporting
confidence: 75%
“…
Newly discovered fluid inclusions in thin sections of Bjurbole chondrules, shergottite EETA79001, lunar meteorite ALH A81005, and Apollo 16 glasses possess physical properties similar to those of fluid inclusions found in thin sections of five stony meteorites recently described by Warner et al (1983). The distribution and physical properties of these new fluid inclusions indicate they may be artifacts of thin section preparation; we suggest that saw coolant was sucked into vacuum vesicles in glasses and minerals through submicroscopic fractures produced during sawing.
…”
supporting
confidence: 56%
See 2 more Smart Citations
“…Ip and Fernandez (1988) estimated the impact rate of large comets, with masses greater than 7 × 10 13 kg, at 1 every 13 million years. Warner et al (1983) reported on fluid inclusions in stony meteorites, but any water release from such a source would be small.…”
Section: Introductionmentioning
confidence: 95%